Ecolinguistic Topics in Indonesian English Textbooks - Alvia Nurrahma Ekasiwi; Barli Bram (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. Ecolinguistics may be one of the newest branches of linguistics. However, it has an important role in the educational field. Through ecolinguistics, students can possess both linguistics and ecological knowledge at the same time. Moreover, the case of environmental issues was getting higher day by day, Thus, it is important to put ecolinguistics representation through the contents of textbooks.  This qualitative research aimed to investigate the portrayal of ecolinguistics aspects in several Indonesian English textbooks. The purpose of this study is to analyze, whether Indonesian English textbooks use ecolinguistic aspects in their topics, words, or sentences or not. Five Indonesian English textbooks published by the Indonesian government were used as data sources. To gather the data, a corpus application, AntCont, was used. The descriptive qualitative approach and corpus approach were used in this study to analyze the contents of the English textbooks. The findings of the study indicated that not all Indonesian English textbooks represented ecolinguistics aspects in their topics, words, and sentences. Only three English textbooks from the total of five English textbooks portrayed ecolinguistic aspects in their contents. It is expected that the study results would improve the global understanding related to the environment and ecolinguistic topics, particularly through English textbooks for students. Keywords: Ecolinguistic topic, ecology, English textbook, EFL, ELT